Determinants of e-hailing service adoption among university students in Peninsular Malaysia - Yan, Eng Xin; Md Jusoh, Zuroni; Zainudin, Norzalina; Osman, Syuhaily (Human Resource Management Academic Research Society, 2024)
This research aims to identify the determinant factors influencing university students' intention to use e-hailing services, including attitude, subjective norm, perceived behavioral control, perceived usefulness, and perceived ease of use. A sample of 200 students from five different universities completed a questionnaire. Analysis with SPSS version 26.0 for Windows revealed significant correlations between the intention to use e-hailing services and attitude (r = 0.938, p = 0.000), subjective norm (r = 0.964, p = 0.000), perceived behavioral control (r = 0.965, p = 0.000), perceived usefulness (r = 0.964, p = 0.000), and perceived ease of use (r = 0.958, p = 0.000). Multiple Linear Regression analysis indicated that subjective norm (B = 0.302) was the most influential factor, followed by perceived behavioral control, perceived usefulness, and perceived ease of use. These findings suggest these factors are crucial in influencing students' decisions. E-hailing companies can develop more effective marketing strategies by focusing on these areas, enhancing adoption and usage among university students. This research also enriches the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM).